2000
DOI: 10.1046/j.1365-2036.2000.014s1094.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat CXC chemokine GRO/CINC‐1 paradoxically stimulates the growth of gastric epithelial cells

Abstract: Summary Background: CXC chemokines such as interleukin (IL)‐8 are neutrophil chemoattractants, the levels of which increase in Helicobacter pylori‐infected gastric mucosa. Many investigators have focused on the chemotactic aspects of IL‐8; however, CXC chemokines are also reported to have angiogenic activity and to serve as remodelling factors. Rat GRO/CINC‐1 is a rodent counterpart of human GROα, a member of the family of CXC chemokines. Gastric mucosa infected with H. pylori is in a state of hyperproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…Studies by Driscoll et al (16) have demonstrated increased proliferation of rat alveolar epithelial cells in response to stimulation by the CXC chemokines MIP-2 or CINC. Increased proliferation and ERK1/2 signaling has also been observed for the rat gastric epithelial cell line RGM-1 following stimulation by CINC (17). Consistent with these studies, epithelial resurfacing of excisional wounds in CXCR2 knockout mice is significantly delayed compared with wild-type animals (30).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Studies by Driscoll et al (16) have demonstrated increased proliferation of rat alveolar epithelial cells in response to stimulation by the CXC chemokines MIP-2 or CINC. Increased proliferation and ERK1/2 signaling has also been observed for the rat gastric epithelial cell line RGM-1 following stimulation by CINC (17). Consistent with these studies, epithelial resurfacing of excisional wounds in CXCR2 knockout mice is significantly delayed compared with wild-type animals (30).…”
Section: Discussionsupporting
confidence: 76%
“…In keeping with this evidence, previous studies have reported that the rat neutrophildirected CXC chemokines MIP-2 and CINC-1 can exert mitogenic effects on alveolar epithelial cells and gastric epithelial cells, respectively (16,17). The CC chemokine MCP-1 has also been reported to induce mitogenic responses in human bronchial epithelial cells (18).…”
Section: Macrophage-inflammatory Protein-3␣ Mediates Epidermal Growthsupporting
confidence: 51%
“…The expected role for expression of these ligands is in the recruitment of leukocytes to sites needed to fight infection and in the homeostasis of the gut epithelium. 23 However, CXCR2 −/− mice remain quite small and do not grow as well as the heterozygous and wildtype mice. A role for CXCR2 in absorption or homeostasis of the gut has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Ishiguro et al [8] reported that in a rat model of trinitrobenzene sulfonic acid (TNBS)-induced colitis, CINC-1 enhances the expression of co-stimulatory molecules on dendritic cells in the mesenteric lymph nodes [8]. In addition, Suzuki et al [9] reported the growthstimulatory effects of CINC-1 on rat gastric epithelia cells.…”
Section: Cinc-1 Functionmentioning
confidence: 99%